Electric Vehicle Impact on the Sustainable Development Goals Considering Renewable Energy Sources Integration - Abdussalam Ali Ahmed; Mahmod Gomah (African Journal of Advanced Pure and Applied Sciences, 2023)
An Electric Vehicle (EV) is considered as the solution for environmental limitation by integrating alternative resources. Besides, traditional vehicles are running against the Sustainable development goals that making a negative impact which can be overcome. This paper focus on the impacts on Renewable Energy Sources (RESs) and EV integration for meeting sustainable development goals such as Sustainable Developments Goal (SDG7) and Climate Action Goal (CAG13) by integrating EV and PV. The aforementioned sustainable developments Goals can be obtained by strategizing methos using Rule-Based Energy Management Strategy (RB-EMS) when integrating RESs into the proposed system. Thus, this study assists to measure the use of alternative sources as discussed in the result section in order to reduce the cost and emission and meet sustainable development goals.